The Effect of Family Nursing on Family Function among Adolescent Pregnancy at Prangku District Sisaket Province - Tammabut, Chutimaporn; Phinyo, Kittiphoom (Journal of The Royal Thai Army Nurses, 2025)
This research is quasi-experimental research with one group pretest - posttest design aimed to examining the effect of family nursing on family function among adolescent pregnancy at Prangku district Sisaket province. The samples consisted of 10 pregnant teenagers, and 10 of those teenager’s family. The sample received the 6-week program. The research instrument consisted of the family nursing guidelines to promote family function in adolescent pregnancy. The health of teenage mom and family handbook, both of these interventions were developed by the researcher. The data was collected by family function questionnaires based on the perception of family and pregnant teenagers. Data was analyzed by using Wilcoxon signed rank test and Mann-Whitney U test. The results revealed that: after intervention, the family function during adolescent pregnancy based on the perception of family and pregnant teenager The family function during adolescent pregnancy based on the perception of family and pregnant teenager higher than before intervention. The different was statistically significantly (P<.05) and the perception of family function between family and pregnant teenager were no difference (P>0.5) These findings suggest relevant healthcare personnel could apply this program to encourage families to be able to take care of pregnant teenagers.